Interview with Robert Mott, October 16, 1971 (Mustang Radio Network, 1971)
[00:00:00] Interviewer introduces topic of professional education, the best example at Cal Poly being the Physical Education Workshops [00:00:34] Interviewer introduces Robert Mott, head of Cal Poly's Men's Physical Education Department [00:01:00] Mott talks about the people attending the workshops for physical education, who they are and where are they from [00:01:25] Mott talks about the goal of the workshops [00:02:17] Mott talks about the number of instructors on campus for these events [00:02:29] Mott talks about the various sponsoring groups of these workshops [00:02:55] Mott discusses how professional educators view the program [00:03:45] Mott talks about some of the famous professional coaches and instructors who helped to develop and lead activities [00:05:43] Interviewer begins to wrap up interview